A model predicting fluindione dose requirement in elderly inpatients including genotypes, body weight, and amiodarone - Moreau, Caroline; Pautas, Eric; Duverlie, Charlotte; Berndt, Celia; Andro, Marion; Mahé, Isabelle; Emmerich, Joseph; Lacut, Karine; Gal, Grégoire Le; Peyron, Isabelle; Gouin-Thibault, Isabelle; Golmard, Jean-Louis; Loriot, Marie-Anne; Siguret, Virginie (Thrombosis and Haemostasis, 2014)
Indandione VKAs have been widely used for decades, especially in Eastern Europe and France. Contrary to coumarin VKAs, the relative contribution of individual factors to the indandione-VKA response is poorly known. In the present multicentre study, we sought to develop and validate a model including genetic and non-genetic factors to predict the daily fluindione dose requirement in elderly patients in whom VKA dosing is challenging. We prospectively recorded clinical and therapeutic data in 230 Caucasian inpatients mean aged 85 ± 6 years, who had reached international normalized ratio stabilisation (range 2.0–3.0) on fluindione. In the derivation cohort (n=156), we analysed 13 polymorphisms in seven genes potentially involved in the pharmacological effect or vitamin-K cycle (VKORC1, CYP4F2, EPHX1) and fluindione metabolism/transport (CYP2C9, CYP2C19, CYP3A5, ABCB1). We built a regression model incorporating non-genetic and genetic data and evaluated the model performances in a separate cohort (n=74). Body-weight, amiodarone intake, VKORC1, CYP4F2, ABCB1 genotypes were retained in the final model, accounting for 31.5% of dose variability. None influence of CYP2C9 was observed. Our final model showed good performances: in 83.3% of the validation cohort patients, the dose was accurately predicted within 5 mg, i.e. the usual step used for adjusting fluindione dosage. In conclusion, in addition to body-weight and amiodarone-intake, pharmacogenetic factors (VKORC1,CYP4F2,ABCB1) related to the pharmacodynamic effect and transport of fluindione significantly influenced the dose requirement in elderly patients while CYP2C9 did not. Studies are required to know whether fluindione could be an alternative VKA in carriers of polymorphic CYP2C9 alleles, hypersensitive to coumarins.
Keywords: Vitamin K antagonist; fluindione; VKORC1; model; elderly